IMPLEMENTASI PERATURAN KEPOLISIAN NOMOR 7 TAHUN 2022 TENTANG KODE ETIK PROFESI DAN KOMISI KODE ETIK KEPOLISIAN NEGARA REPUBLIK INDONESIA TERHADAP SELEKSI PENERIMAAN ANGGOTA POLRI DI KEPOLISIAN RESOR ROKAN HULU - Candra Purnomo; Yetti Yetti; Rudi Pardede (Yayasan Pendidikan Islam Almatani, 2025)
Article 10 paragraph (4) letter f and letter g of Police Regulation Number 7 of 2022 concerning the Indonesian National Police Professional Code of Ethics regulates the prohibition on members and officials of the Indonesian National Police from receiving rewards and promising to pass the selection process for members of the Indonesian National Police and development education. The purpose of this research is to analyze the implementation of this regulation on the selection process for members of the Indonesian National Police at the Rokan Hulu Police; to analyze the inhibiting factors and efforts to overcome these obstacles. The implementation of Article 10 paragraph (4) letter f and letter g of Police Regulation Number 7 of 2022 on the selection process for members of the Indonesian National Police at the Rokan Hulu Police has not been running well from 2023 to 2025, as evidenced by the existence of Indonesian National Police officials who received rewards and promised to pass the selection process for members of the Indonesian National Police at this police station, accompanied by law enforcement that has not been as it should be. The inhibiting factor is the legal factor, efforts to overcome it if there are general criminal reports and violations of the code of ethics simultaneously, then the decision of the code of ethics trial is not influenced by the resolution of general crimes that prioritize restorative justice. The factor of law enforcement officers, efforts to overcome this is that the local police often hold spiritual and mental guidance activities for their members; The local police institution always reminds its members and ranks not to live a hedonistic and luxurious life; all ranks of the police in carrying out their duties, functions, and authorities are based on the Indonesian National Police's professional code of ethics, Tribrata and Catur PrasetyaThe police cooperative provides low-interest loans and easy loan and repayment terms for business capital. Community factors, in order to overcome this, the police continue to provide free coaching and training programs for local communities who wish to participate in the selection process for Polri members and continuously socialize the program; conduct legal socialization to the community regarding the selection process for prospective Polri members; Polri members refuse to accept money from the community; within the Polri, strict sanctions are imposed on officials and their ranks; externally, the Polri provides counseling to the community directly and through social media platforms that to become a Polri member, bribes and insiders are not used. Cultural factors, in order to overcome this, the police conduct legal socialization to the community regarding the prohibition and legal sanctions for people who give bribes to state officials.